PENGARUH LOCUS OF CONTROL DAN BUDAYA PATERNALISTIK TERHADAP KEEFEKTIFAN PENGANGGARAN PARTISIPATIF DALAM PENINGKATAN KINERJA MANAJERIAL - RENY MUSTIKAWATI (Jurnal Bisnis dan Akuntansi, 1999)
The effect of participation in the budgeting process to improve managerial performance is an interesting area of research for many years. It has been postulated that participative budgeting has a positive effect on managerial performance. Several prior researches, held to examine the relationship between participative budgeting and managerial performance, have yield the inconsistency results. To overcome this phenomenon, some researchers suggest to use contigency approach which looks at the moderating effect of both locus if control (internal vs external) and cultural dimension (paternalism). This research examines the effect of locus of control and paternalism on the effectiveness of participative budgeting to increase managerial performance. The responses of 56 managers, drawn from a cross department on Indonesian companies, were analyzed by multiple regression model. The result indicates that there is a significantly positive relationship between participative budgeting and managerial performance. And also, locus of control doesn't moderate the relationship between participative budgeting and managerial performance. This study also found that paternalism moderates the relationship between participative budgeting and managerial performance.